USING HEATING AND VACUUM AS A NEW SYSTEM TO ACHIEVE SHORT COOKING TIME FOR PRODUCING BLACK HONEY - Tarek FOUDA; Ali HASSAN; Mohamed GEASA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The experiments were conducted at Agricultural Engineering Department Laboratory, Faculty of Agriculture Al-Azhar University, Assiut Governorate during 29th of July to 15th of November 2022, in order to develop and manufacture a small unit for producing high quality black honey depends on heating and vacuum system. Also, to determine the optimum treatment forsafe method taken into consideration the environmental impact and evaluate changes in black honeyquality during cooking. This unit consisting of pan vessel, heater, compressor, condenser, rectifier, vessel receiver oil and smart control system.The experimental treatments for black honey cooking unit were tested on three heating temperatures different at 200, 350 and 500 oC and four vacuum levels at 150, 300, 450 and 600 mbar and atmospheric pressure.The results shows a decreasing of cooking time at vacuum pressure less than from atmospheric pressure. At vacuum pressure samples, cooking time ranged from 30 to 172 minutes. The highest cooking time was (177, 77and 40 minutes) recorded with atmospheric pressure at different heating temperatures (200, 350 and 500oC), respectively. The lowest cooking time was (155, 64and 30 minutes) recorded with vacuum pressure (-600 mbar) with different heating temperature (200, 350 and 500oC), respectively. The data shows an increasing of evaporation rate of water from sugar cane juice at vacuum pressure more than from atmospheric pressure. At vacuum pressure samples, evaporation rate ranged from 4.53to 26 gH2O/min. The lowest evaporation rate was (4.41, 10.13 and 19.50 gH2O/min) recorded with atmospheric pressure at different heating temperatures (200, 350 and 500oC), respectively. The highest evaporation rate was (5.03, 12.19 and 26 gH2O/min) recorded with vacuum pressure (-600 mbar) with different heating temperature (200, 350 and 500oC), respectively.